Future Connectivity for Disaster and Emergency Point of Care - Yu, Jimmy N. (2010)
OBJECTIVE: The goal of this paper is to identify strategies for connectivity that will optimize point-of-care testing (POCT) organized as small-world networks in disaster settings. METHODS: We evaluated connectivity failures during the 2010 Haiti Earthquake, applied small-world network concepts, and reviewed literature for point-of-care (POC) connectivity systems. RESULTS: Medical teams responding to the Haiti Earthquake faced connectivity failures that affected patient outcomes. Deploying robust wireless connectivity systems can enhance the efficiency of the disaster response by improving health care delivery, medical documentation, logistics, response coordination, communication, and telemedicine. Virtual POC connectivity education and training programs can enhance readiness of disaster responders. CONCLUSIONS: The admirable humanitarian efforts of more than 4000 organizations substantially impacted the lives of earthquake victims in Haiti. However, the lack of connectivity and small-world network strategies, combined with communication failures, during early stages of the relief effort must be addressed for future disaster preparedness.